170 Primary Breast Lymphoma-Mimicking Inflammatory Breast Disease: A Case Report. (4th May 2021) - Alam, R; Basak, B; Ahsan, A; Gupta, A S; Islam, S; Akther, S M Q
Abstract: Primary breast lymphoma (PBL) is an unusual clinical entity accounting for 0.4–0.5% of all breast neoplasms. The usual presentation includes a painless palpable mass similar to that of breast carcinoma. Diffuse large B-cell lymphoma (DLBCL) is the most common identifiable type of PBL based on the histopathological examination. We report an unusual case of 22 years old Bangladeshi woman presented with a 6-month history of a lump on left breast. Although the lump was initially small, it began a rapid growth after 4 months. The swelling was localized and did not show any skin involvement or discharge and as she didn't have any positive familial history of breast carcinoma her primary attending physician diagnosed it as a case of breast abscess. When local incision and drainage proved ineffective, she was referred to us. After doing an immunohistochemistry from incisional biopsy the diagnosis was confirmed as Diffuse Large B-cell Lymphoma. The patient was treated initially by chemotherapy with CHOP therapy followed by wide local excision. Early and accurate diagnosis of PBL is crucial for selecting the appropriate MDT treatment strategies to avert potentially harmful surgical interventions.